Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s10811-019-02010-5
|View full text |Cite
|
Sign up to set email alerts
|

Biosecurity policy and legislation for the global seaweed aquaculture industry

Abstract: Each year a significant proportion of global food production is lost to pests and diseases, with concerted efforts by government and industry focussed on application of effective biosecurity policies which attempt to minimise their emergence and spread. In aquaculture the volume of seaweeds produced is second only to farmed fish and red algal carrageenophytes currently represent approximately 42% of global production of all seaweeds. Despite this importance, expansion of the seaweed sector is increasingly limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Meta-barcoding evidence suggests the existence of a hidden diversity of pathogens that are yet to be described (Badis et al, 2019). Despite the well-documented lessons learnt from the aforementioned oyster and crustacean industries, these examples and subsequent assessments, highlight a comparative lack of biosecurity awareness and implementation in the seaweed industry at both an international (Campbell et al, 2019) and national level (Kambey et al, 2020;Mateo et al, 2020;Rusekwa et al, 2020).…”
Section: Novel Cons Ervation Challeng E S B Roug Ht By Alg Al Cultimentioning
confidence: 99%
See 3 more Smart Citations
“…Meta-barcoding evidence suggests the existence of a hidden diversity of pathogens that are yet to be described (Badis et al, 2019). Despite the well-documented lessons learnt from the aforementioned oyster and crustacean industries, these examples and subsequent assessments, highlight a comparative lack of biosecurity awareness and implementation in the seaweed industry at both an international (Campbell et al, 2019) and national level (Kambey et al, 2020;Mateo et al, 2020;Rusekwa et al, 2020).…”
Section: Novel Cons Ervation Challeng E S B Roug Ht By Alg Al Cultimentioning
confidence: 99%
“…Seaweeds in their current early state of domestication and with their aquatic habitat sit at the crossroads of regulatory frameworks. Within the national jurisdiction zone, seaweeds-whether cultivated or not-are regulated under the Nagoya Protocol, as their aquatic origin currently excludes them from being considered under the International Treaty for Plant Genetic Resources for Food and Agriculture (ITPGRFA) (Campbell et al, 2019). The Nagoya Protocol gives countries sovereignty over the genetic resources within their national jurisdiction.…”
Section: A G Overnan Ce In Need Of Adap Ting To R Apid Chang E Smentioning
confidence: 99%
See 2 more Smart Citations
“…Biosecurity measures related to seaweed aquaculture, however, are absent from the literature, with the exception of Sulu et al (2004), which describes basic quarantine protocols. Campbell et al (2020) reported four biosecurity policy challenges faced by the seaweed industry globally, which should be addressed to make the industry more robust and sustainable. These challenges included (1) inconsistent terminology for the inclusion of seaweeds in regulatory frameworks, (2) limited guidance for the responsibility of implementation of biosecurity measures, (3) insufficient evidence to develop disease and pest-specific policies and (4) lack of a coherent approach to seaweed biosecurity risk management in international policies.…”
Section: Introductionmentioning
confidence: 99%